Revisiting gender-fair language and stereotypes – A comparison of word pairs, capital I forms and the asterisk - Schunack Silke; Binanzer Anja (Zeitschrift für Sprachwissenschaft, 2022)
In this paper we replicated two influential studies on gender-fair language that investigated how gender-fair language influences stereotype perception and recall of exemplars. We also updated the original studies to assess new forms of gender-fair language. A first set of studies replicated Gabriel et al. (2008) by eliciting gender proportion ratings for occupational nouns from adult German native speakers for word pairs, capital I forms and the asterisk. Results were mixed with effects mainly for female-biased nouns. Only the non-binary asterisk form (Lehrer*innen) showed an increase of women for male-biased nouns. A third study replicated Stahlberg and Sczesny’s (2001) naming study. Here, the number of women answers was higher than in the original study and increased when using gender-fair language with a larger increase for capital I forms (LehrerInnen) than for word pairs (Lehrer und Lehrerinnen). Overall, the effects of word pair forms were weaker than those of other forms of gender-fair language.